Alteration of the Kinetics of Thrombin-catalyzed Hydrolysis of Amino Acid Ester Substrates by Sodium Cholate and Other Steroids - Cole, Edmond R. (Thrombosis and Haemostasis, 1974)
Thrombin-catalyzed hydrolysis of TAME proceeds by an initial zero-order phase which later falls off into an apparent first order reaction as substrate becomes limiting. Optimum amounts of sodium cholate not only accelerated TAME hydrolysis but also altered its kinetics to apparent zero-order to complete substrate hydrolysis. As this implies, the rate of hydrolysis in the presence of cholate was found to be independent of substrate concentration, provided concentrations of TAME and cholate were low enough to prevent precipitation of some TAME-cholate as an insoluble complex. The formation of a soluble complex composed of polymeric molecules of TAME and cholate may explain both the acceleration and the change in reaction order. Although the pH and temperature optima for TAME hydrolysis by thrombin were not altered by the presence of cholate, the degree of acceleration increased with rising pH and temperature on the ascending portion of the curves. This is believed to be due to the greater solubility of the TAME-cholate complex. The effects of cholate on thrombin-catalyzed hydrolysis of other arginine esters as well as esters of lysine, histidine and phenylalanine were also studied.Solutions of sodium desoxycholate and androsterone-3-sulfate accelerated TAME hydrolysis as did supensions of testosterone, etiocholanolone, androsterone, androsterone-3-hemisuccinate and pregnandiol-3-glucuronidate. However, isoandrosterone, progesterone, pregnandiol, estradiol, estrone, estriol, estrone-3-sulfate, cholesterol, corticosterone, hydrocortisone and hydrocortisone-3-phosphate had no significant effect on TAME hydrolysis by thrombin. The ability of the androgenic hormones to accelerate hydrolysis appeared to depend to some extent on the configuration of the substituent group at C3 and the hydrogen at C5. Androsterone-3-hemisuccinate was, like cholate, able to accelerate the hydrolysis of TAME at apparent zero-order kinetics to complete substrate hydrolysis.